Effectiveness of Sitting in Older Adults with Altered Consciousness Admitted to a General Ward: A Case Series - Candoni, Gerardo; Lecuona, Daniela; Troia, Carolina (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: Uprighting subjects with altered consciousness, either using a tilt table or seated positioning, enhances their behavior, arousal, and consciousness levels. The objective was to describe the physiotherapeutic management of a verticalization program in subjects with altered consciousness in the acute and subacute stages. Materials and Methods: Subjects included were those diagnosed with altered consciousness and fluency in Spanish. Those missing 20% of the data were excluded. A seated positioning program was carried out for 30 minutes over 10 days, and changes in consciousness levels were measured using the revised coma scale and the presence of adverse effects. Results: Of the eight subjects included in the study, seven showed improvements in their level of consciousness, and only one subject experienced adverse effects during the seated positioning program. One subject was excluded from the study due to incomplete data. Conclusion: This study provides a comprehensive description of the physiotherapeutic management of a verticalization program for subjects with altered consciousness during the acute and subacute stages. The majority of the subjects included demonstrated an improvement in their level of consciousness.